Opposite effects of bFGF and TGF-beta on collagen metabolism by human periodontal ligament fibroblasts - Gonzales Silverio-Ruiz, Karina; Traverso Martinez, Aurora Esmeralda; Pompermaier Garlet, Gustavo; Fregonesi Barbosa, Carolina; Santana Silva, Joao; Barreto Cicarelli, Regina Maria; Valentini, Sandro Roberto [UNESP]; Georges Abi-Rached, Ricardo Sarnih; Rossa, Carlos Junior (Elsevier B.V., 2007)
This study evaluated the effects of bFGF and TGF-beta, individually and combined, on cell proliferation and collagen metabolism. Primary human periodontal ligament cells were stimulated with two concentrations (I and 10 ng/ml) of each growth factor, both individually and combined. Proliferation was determined by a commercial biochemical assay. Real time RT-PCR determined gene expression of NMP-1 and -2, collagen types I and III, TIMP-1, -2 and -3. Autocrine effects on synthesis of bFGF and TGF-beta were evaluated by ELISA. Only TGF-beta, either isolated or associated with bFGF, significantly increased cell proliferation. TGF-beta had anabolic effects, increasing expression of type I and III collagen as well as of TIMPs, whereas bFGF had opposite effects. When bFGF and TGF-beta were associated, the anabolic effects prevailed. Synthesis of TGF-beta was induced only by the association of lower concentrations of the growth factors, whereas there was a dose-dependent production of bFGF. It is concluded that bFGF had a predominantly catabolic effect, and TGF-beta exerted an anabolic effect on hPDL cells. (c) 2007 Elsevier Ltd. All rights reserved.
Keywords: human periodontal ligament cells; transforming growth factor beta; basic fibroblast growth factor; collagen; matrix metalloproteases; tissue inhibitor of matrix metalloproteases; periodontal regeneration